2022
DOI: 10.1136/bmjopen-2021-055458
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of women with gestational diabetes mellitus using mutually exclusive categories based on the International Association of Diabetes and Pregnancy Study Groups criteria for the development of postpartum dysglycaemia: a retrospective cohort study

Abstract: ObjectivesWomen with gestational diabetes mellitus (GDM) are more predisposed to develop postpartum diabetes mellitus (DM). This study aimed to estimate the relative risk (RR) of postpartum dysglycaemia (prediabetes and DM) using mutually exclusive categories according to the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria cut-off points in patients with GDM, so as to establish a risk-stratification method for developing GDM management strategies.Design, setting and participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Two recent additional studies, from Canada ( n = 20 513 with GDM; median follow‐up of 4.4 years) and Singapore ( N = 942 with GDM, evaluated at 6–12 weeks postpartum), explored the relationship between the OGTT type and the future risk of diabetes for women diagnosed using IADPSG criteria. 8 , 9 Both studies found significant differences in future risk of diabetes based on OGTT type. Given that GDM diagnosed using IADPSG criteria is milder with a lower risk of future diabetes than that with other criteria, identifying high‐risk women with a history of IADPSG criteria becomes even more crucial for judicious use of limited resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent additional studies, from Canada ( n = 20 513 with GDM; median follow‐up of 4.4 years) and Singapore ( N = 942 with GDM, evaluated at 6–12 weeks postpartum), explored the relationship between the OGTT type and the future risk of diabetes for women diagnosed using IADPSG criteria. 8 , 9 Both studies found significant differences in future risk of diabetes based on OGTT type. Given that GDM diagnosed using IADPSG criteria is milder with a lower risk of future diabetes than that with other criteria, identifying high‐risk women with a history of IADPSG criteria becomes even more crucial for judicious use of limited resources.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the meta‐analysis was not possible for 1‐h values due to inadequate data. Two recent additional studies, from Canada ( n = 20 513 with GDM; median follow‐up of 4.4 years) and Singapore ( N = 942 with GDM, evaluated at 6–12 weeks postpartum), explored the relationship between the OGTT type and the future risk of diabetes for women diagnosed using IADPSG criteria 8,9 . Both studies found significant differences in future risk of diabetes based on OGTT type.…”
Section: Introductionmentioning
confidence: 99%